Graphene oxide–polythiophene hybrid with broad-band absorption and photocatalytic properties - Wang, Shuai (2013)
Hybrid graphene oxide (GO)/poly(3-hexylthiophene-2,5-diyl) (P3HT) sheets are assembled via π–π interaction and carefully isolated from the nonreacted precursors. The mutual influence of the two phases can be sharply manifested in this layer-to-layer configuration because it is undiluted by excess of one phase. To investigate the optical properties of the hybrid and possible synergistic interactions, we applied photothermal deflection spectroscopy (PDS) and pump–probe techniques. For the first time, the photocatalytic performance of these hybrids was investigated to correlate with their optical properties. The GO–P3HT hybrid demonstrates broad-band absorption and ultrafast charge transfer (1.4 ps) and acts as an excellent photocatalyst for the Mannich reaction (93% yield).